2021
DOI: 10.1007/s10237-021-01521-w
|View full text |Cite
|
Sign up to set email alerts
|

Mechano-regulated cell–cell signaling in the context of cardiovascular tissue engineering

Abstract: Cardiovascular tissue engineering (CVTE) aims to create living tissues, with the ability to grow and remodel, as replacements for diseased blood vessels and heart valves. Despite promising results, the (long-term) functionality of these engineered tissues still needs improvement to reach broad clinical application. The functionality of native tissues is ensured by their specific mechanical properties directly arising from tissue organization. We therefore hypothesize that establishing a native-like tissue orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 489 publications
(971 reference statements)
0
10
0
Order By: Relevance
“…3E , 4E and 5E ), previous experiments in pulmonary arteries have shown an increase in Notch3 expression driving arterial thickening in hypertension ( Li et al, 2009 ; Qiao et al, 2012 ). This suggests that the role and mechanosensitive behavior of Notch in hypertension may depend on the location in the vasculature, which would be in line with the highly context- and tissue-specific nature of Notch ( Stassen et al, 2020 ; Karakaya and Van Asten et al 2022 ). To our knowledge, Notch mechanosensitivity in VSMCs has only been investigated in the systemic circulation ( Morrow et al, 2005 ; Loerakker et al, 2018 ).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…3E , 4E and 5E ), previous experiments in pulmonary arteries have shown an increase in Notch3 expression driving arterial thickening in hypertension ( Li et al, 2009 ; Qiao et al, 2012 ). This suggests that the role and mechanosensitive behavior of Notch in hypertension may depend on the location in the vasculature, which would be in line with the highly context- and tissue-specific nature of Notch ( Stassen et al, 2020 ; Karakaya and Van Asten et al 2022 ). To our knowledge, Notch mechanosensitivity in VSMCs has only been investigated in the systemic circulation ( Morrow et al, 2005 ; Loerakker et al, 2018 ).…”
Section: Discussionmentioning
confidence: 63%
“…An increased control over tissue G&R via Notch manipulations may also aid in improving tissue engineered blood vessels and heart valves ( Carlson et al, 2007 ; Zohorsky and Mequanint, 2021 ; Tiemeijer et al, 2022 ; Karakaya and Van Asten et al 2022 ). Such manipulations may consist of immobilizing external Jagged ligands to scaffolds ( Beckstead et al, 2006 ; Putti et al, 2019a , 2019b ), a technique that has previously been found beneficial for tissue development ( Beckstead et al, 2006 ; Wen et al, 2014 ; Dishowitz et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 40 Importantly, similar processes appear to be operative in tissue engineered constructs, both in vitro and in vivo. 46 Conceptually, this homeostatic tendency is illustrated easily for a straight segment of a blood vessel subjected to a steady pressure-driven flow. Consider cell-sensed normalized differences ( ) in stress from homeostatic values that tend to be minimized via a homeostatic response, namely
Figure 1 Schema to illustrate mechanobiological control of mechanical homeostasis at the cell level.
…”
Section: Foundations: a Brief On Mechanobiologymentioning
confidence: 99%
“…In the canonical Notch pathway, Jagged or Delta-like ligands interact with membrane-bound Notch receptors of adjacent cells, resulting in the cleavage of the Notch intracellular domain (NICD), which then translocates to the nucleus to regulate the transcription of Notch target genes. Numerous studies have revealed that Notch strongly influences the behavior of SMCs in health and disease (Iso et al 2003;Gridley 2007;Del Monte et al 2011;Baeten and Lilly 2017;Mašek and Andersson 2017;Li and Kong 2020;Ristori et al 2021;Karakaya et al 2022b), including during many instances of G&R. The Notch pathway is also increasingly recognized as mechano-sensitive (Stassen et al 2020, Karakaya andVan Asten et al 2022a). For example, Notch signaling between SMCs responds to changes in strain by altering the expression of Notch receptors and Jagged ligands (Morrow et al 2005;Loerakker et al 2018;Karakaya et al 2022a).…”
Section: Introductionmentioning
confidence: 99%